Investigating parametric effects on performance of a high‐temperature URSOFC. (30th December 2014) - Su, Ay; Ferng, Yuh‐Ming; Wang, C. B.
Summary The aim of this paper is to investigate the effects of variable parameters on the performance of a unitized regenerative solid oxide fuel cell (URSOFC) using a two‐dimensional axisymmetric simulation model. This model was validated using the performance curves of an in‐house button‐type URSOFC. The parameters studied include the operating temperature and the porosity, tortuosity, and grain diameter of the electrodes while the URSOFC is operated in the solid oxide fuel cell mode and the solid oxide electrolyzer cell (SOEC) mode. The predicted results show that the temperature and the electrode porosity have a beneficial effect on the performance of the URSOFC because of an enhancement of the electrochemical reactions and the species mass transfer, respectively. However, when the URSOFC is operated in the SOEC mode, the cell performance decreases as the electrode porosity increases. This indicates that the decreasing reaction active sites as a result of the higher porosity have a dominant effect on the performance in the SOEC mode. The cell performance also decreases as the tortuosity and grain diameter of the electrodes increase. In addition, the effect of the electrode grain diameter on the cell performance is predicted to be insignificant for the URSOFC operated in the SOEC mode. The results of investigations presented in this paper can assist in the optimal design and management of a URSOFC. Copyright © 2014 John Wiley & Sons, Ltd.